LEGAL REGULATION OF DECENTRALIZED INFORMATION PLATFORMS: PROBLEMS AND THE SUGGESTED PRIVATE-LAW APPROACH TO THEIR SOLUTION IN UKRAINE - Kud A. А. (Theory and Practice of Public Administration, 2021)
The paper is devoted to critical understanding of the main existing approaches to legal regulation of digital platforms and digital solutions based on blockchain technology. The aim of this paper is to substantiate the modern scientific and applied approach to regulation of decentralized information platforms in Ukraine, which is based on private law. This approach is the basis of the innovative Draft Law of Ukraine No. 4328, which offers both regulation of the unregulated area of virtual assets and a method of increasing the use of decentralized platforms, through which such regulation can be carried out taking into account the interests of the state. The paper contains an analysis of legal issues in private and public law. Amendments to Ukrainian legislation have been suggested in the paper. It has been concluded that blockchain-based decentralized information platforms open an unexpected opportunity to change the model of the state in terms of fund flows into public budget. This is due to a significant risk reduction when concluding and executing contracts in the public sector. Furthermore, the author concludes that the subjects of platform interaction can create rules of mutual interaction, determine the procedure for resolving disputes and adjudicate relevant disputes without resorting to existing national, international and supranational instruments of regulation and coercion. Therefore, when participants of the information platform are forced to interact with legal entities of public law (state and municipal institutions, budget funds, etc.), which set strict requirements for compliance with certain rules as conditions of access to their services (public, information, banking, etc.), then participants of the platform are forced to follow the established rules. As a result, the establishment of clear and simple procedures and rules of conduct when receiving services through digital platforms is a trigger for governments to encourage investments in the development of digital business.